Modelling of the Inverse Creep of Road Bitumen Modified With SBS Copolymer - Mieczysław Słowik (The Baltic Journal of Road and Bridge Engineering, 2012)
Polymer modified road bitumens, being examples of viscoelastic materials, are very interesting with respect to rheology. The phenomenon of inverse creep (retarded strain recovery) observed in samples of asphalt binders modified by the addition of SBS copolymer was analyzed in the present paper. Laboratory tests of strain recovery were conducted on samples of the three selected asphalt binders: the 50/70 penetration grade base bitumen and binders modified by the addition of 4% and 8% of the SBS copolymer. The extended procedure for the determination of elastic recovery was used as the research method. The results of the experiment were approximated using three linear viscoelastic rheological models: Burgers, Dual Kelvin+Newton and Dual Kelvin+Maxwell. When analyzing the results of modelling carried out by using the Burgers model it has been found that they were not satisfactory. Much greater compatibility of modelling and experiment results (R2 > 0.99) was achieved by using models containing the dual Kelvin element.